Laparoscopic anatomical segment 3 segmentectomy for hepatocellular carcinoma accompanied by hypoplasia of the right hepatic lobe. Issue 7 (10th July 2019) - Yamane, Hisoka; Yoshida, Sachiko; Yoshida, Toshihiko; Nishi, Masayasu; Yamagishi, Takashi; Goto, Hironobu; Otsubo, Dai; Furutani, Akinobu; Matsumoto, Taku; Fujino, Yasuhiro; Tominaga, Masahiro
Abstract: We report a case of laparoscopic anatomical segment 3 segmentectomy for hepatocellular carcinoma (HCC) accompanied by hypoplasia of the right hepatic lobe. An 80-year-old man was admitted with a suspicion of HCC diagnosed by computed tomography during follow-up for thyroid cancer. Dynamic computed tomography showed 40-mm HCC in segment 3 and hypoplasia of the right hepatic lobe with the Chilaiditi sign. We performed laparoscopic anatomical segment 3 segmentectomy. There were no postoperative complications, and the patient was discharged 6 days postoperatively. This procedure can be performed safely and is technically feasible, but special attention should be paid to anatomical alterations to avoid fatal surgical complications.